2016
DOI: 10.1534/g3.116.027508
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections Between RNA-Processing Pathways Revealed by a Sequencing-Based Genetic Screen for Pre-mRNA Splicing Mutants in Fission Yeast

Abstract: Pre-mRNA splicing is an essential component of eukaryotic gene expression and is highly conserved from unicellular yeasts to humans. Here, we present the development and implementation of a sequencing-based reverse genetic screen designed to identify nonessential genes that impact pre-mRNA splicing in the fission yeast Schizosaccharomyces pombe, an organism that shares many of the complex features of splicing in higher eukaryotes. Using a custom-designed barcoding scheme, we simultaneously queried ∼3000 mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 86 publications
(98 reference statements)
5
20
0
Order By: Relevance
“…In contrast to smu1-4 and cwc16a-1, the two GFP-weak mutants reported here, prp8-10 and rtf2-4 showed generally reduced splicing efficiency of GFP premRNA, leading to increased accumulation of the unspliced primary transcript. The overall reduced splicing efficiency in these mutants is consistent with core spliceosomal roles of PRP8 (Pleiss et al 2007) and possibly RTF2 (Larson et al 2016), although a regulatory role through ubiquitination has also been suggested for RTF2 (Sasaki et al 2015).…”
Section: Mechanistic Aspects Of Smu1 and Cwc16a Activity In Splicingsupporting
confidence: 69%
“…In contrast to smu1-4 and cwc16a-1, the two GFP-weak mutants reported here, prp8-10 and rtf2-4 showed generally reduced splicing efficiency of GFP premRNA, leading to increased accumulation of the unspliced primary transcript. The overall reduced splicing efficiency in these mutants is consistent with core spliceosomal roles of PRP8 (Pleiss et al 2007) and possibly RTF2 (Larson et al 2016), although a regulatory role through ubiquitination has also been suggested for RTF2 (Sasaki et al 2015).…”
Section: Mechanistic Aspects Of Smu1 and Cwc16a Activity In Splicingsupporting
confidence: 69%
“…The Drosophila homolog, Yantar, was identified in a genetic deletion screen of lethal recessive mutants for factors that regulate hemocyte development; loss of Yantar is pupal lethal but leads to overproduction of hemocytes in larvae (Sinenko et al 2004). In a reverse genetic screen for factors that affect splicing efficiency in Schizosaccharaomyces pombe, deletion of the fission yeast homolog SPCC162.01c led to both the accumulation of unspliced forms of some messages and increased splicing efficiency for others (Larson et al 2016). SNRNP27 ′ s high enrichment in arginine and lysine residues leaves a very limited number of peptides that can be observed in mass spectrometry proteomic experiments after tryptic digest.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we published the results of a quantitative screen for mutant strains which display splicing defects (Larson et al 2016). Using a sequencing-based approach, we were able to precisely and systematically measure the splicing efficiency of two endogenous transcripts in the background of ~3000 strains, each containing a deletion of a single, non-essential S. pombe gene.…”
mentioning
confidence: 99%